2013
DOI: 10.1111/1365-2745.12045
|View full text |Cite
|
Sign up to set email alerts
|

Above‐ and below‐ground herbivory effects on below‐ground plant–fungus interactions and plant–soil feedback responses

Abstract: Summary 1.Feeding by insect herbivores can affect plant growth and the concentration of defense compounds in plant tissues. Since plants provide resources for soil organisms, herbivory can also influence the composition of the soil community via its effects on the plant. Soil organisms, in turn, are important for plant growth. We tested whether insect herbivores, via their effects on the soil microbial community, can influence plant-soil feedbacks. 2. We first examined the effects of above-ground (AG) and belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Such speciesspecific microbial profiles can influence the performance of other plants that grow later in the same soil (Kostenko et al, 2012;Bezemer et al, 2013;Kos et al, 2015;Heinen et al, 2018). This process is known as plant-soil feedback and can be an important driver of plant community dynamics (Kardol et al, 2006).…”
Section: Plant-soil Feedback Effects On Plant-insect Interactions In mentioning
confidence: 99%
“…Such speciesspecific microbial profiles can influence the performance of other plants that grow later in the same soil (Kostenko et al, 2012;Bezemer et al, 2013;Kos et al, 2015;Heinen et al, 2018). This process is known as plant-soil feedback and can be an important driver of plant community dynamics (Kardol et al, 2006).…”
Section: Plant-soil Feedback Effects On Plant-insect Interactions In mentioning
confidence: 99%
“…A study using ragwort plants ( Jacobea vulgaris ) showed that both above- and below-ground herbivory gave specific effects on the composition of the soil fungal community, possibly by changing root exudation. Remarkably, these changes affected interactions of preceding plants with aboveground herbivores and parasitoids, providing evidence that herbivory influences plant–soil feedback responses via changes in the community of soil-borne microbes (Kostenko et al, 2012; Bezemer et al, 2013). Evidence that root herbivory influences root-associated microbes via changes in root exudation was also found in maize.…”
Section: Plant-mediated Effects Of Insect Herbivores On Non-pathogenimentioning
confidence: 99%
“…The belowground herbivorous insect Agriotes lineatus L. negatively affects the composition of fungal communities in the ragwort ( Jacobaea vulgaris ) rhizosphere (Kostenko et al, 2012). More specifically, infestation by the belowground insect wireworm ( Agriotes lineatus L.) leads to the accumulation of the major plant defense compounds pyrrolizidine alkaloids in ragwort plants and reduces the levels of the pathogenic fungus Fusarium oxysporum in roots (Bezemer et al, 2013). By contrast, feeding by western corn rootworm larvae ( Diabrotica virgifera virgifera ) increases the density of the bacterial and fungal communities in maize ( Zea mays L.) roots.…”
Section: Introductionmentioning
confidence: 99%